O caso dos judeus laicos: a complexidade das identidades étnicas e religiosas nas classificações censitárias (The Jewish Laic: the complexity of the ethnic and religious identities in the census classifications) - DOI: 10.5752/P.2175-5841.2013v11n32p1525 - Rodrigues, Denise dos Santos (Horizonte, 2013)
This article evaluates the impact of the contemporary transformations on traditional religions as the Judaism, that may adopt a secular expression, interfering in the control of its presence in a territory. The isolation of certain ethnic groups inside the field reserved to religion in the census classification may confuse the interpretation of the oscillations of certain goups, once it can produce a camouflage of the real numeric representation. We remind that a member of an ethnic group can feel free to assume a religious identity distant of his familial tradition or, still, to remove the religious elements of his biography, becoming a person without religion. So, at the same time that the census fields that are selfdeclared, with no need of comprobation ratifies the full exercise of the individual freedom in an scenery of high reflexivity, it may invite people to transit freely, breaking up with traditional liaisons, opting for alternative identities, sometimes distant of its ethnic origin.